New Exact Solutions for New Model Nonlinear Partial Differential Equation - A. Maher; H. M. El-Hawary; M. S. Al-Amry (Journal of Applied Mathematics)
In this paper we propose a new form of Padé-II equation, namely, a combined Padé-II and modified Padé-II equation. The mapping method is a promising method to solve nonlinear evaluation equations. Therefore, we apply it, to solve the combined Padé-II and modified Padé-II equation. Exact travelling wave solutions are obtained and expressed in terms of hyperbolic functions, trigonometric functions, rational functions, and elliptic functions.